Non-verbal Salesperson Behaviour in the B2B Environment - Thümler, Nico (2023)
According to research, 90 % of mutual understanding is based on nonverbal behaviors. But contrary to expectations, research on nonverbal behavior in the B2B context is scarce. In this research, I investigate the role of nonverbal behaviors in face-to-face situations of B2B sales in Germany as a prototype low-context culture. Thus, I conduct a three-step research approach. Firstly, I review the literature with bibliometric techniques and propose a conceptual model providing the knowledge base scholars and practitioners can trust. That is based on a dataset of 3,084 articles. Secondly, I lead in-depth expert interviews with 11 salespeople to under-stand the experiences and worlds of thoughts of B2B salespeople. Thirdly, I combine the re-sults of the bibliometric as well as the phenomenological analysis to propose an empirical model of nonverbal behavior in German B2B sales. The results show that nonverbal behavior plays a central role in German B2B sales with significant effects on empathy, customer orien-tation, and sales performance, and explains 69 % of the variance of sales performance. Through customer orientation as a mediator, nonverbal behavior has a strong indirect effect on sales performance. There are no moderating effects for gender. The model provides a starting point for cross-cultural investigations of nonverbal behavior. For practice, the model offers a scientifically sound basis for training salespeople. Salespeople with high-quality nonverbal behavior not only sell better but are more empathetic and customer oriented. They are also more satisfied with their jobs.